Social cohesion among healthcare workers during COVID-19: Qualitative research in Indonesia, Nepal, and Vietnam - Ha Nguyen Thanh; Ida Ayu Sutrisni; Samita Rijal; Aakriti Pandey; Thao Phuong Tran; Ragil Dien; Yen Nguyen Thi Hong; Diana Timoria; Dewi Friska; Aria Kekalih; Claus Bogh; Abhilasha Karkey; et al. (SSM: Qualitative Research in Health, 2024)
Existing literature has portrayed numerous challenges that healthcare workers (HCWs) faced during the COVID-19 pandemic, such as heightened risks of transmission against the scarcity of protective equipment, burgeoning workload, and emotional distress, to name a few. However, most studies explored HCWs' experiences at the individual level rather than examining the collective responses. Exploring these experiences could reveal the social-cultural locality of the pandemic while identifying the system constraints in public health emergencies. As part of a mixed-method study on COVID-19 pandemic impacts, we analysed qualitative interview data with 129 HCWs and health-related staff to explore their experiences during the pandemic between 2020 and 2021 in Vietnam, Indonesia, and Nepal. Using Bahers' sociological framework, Community of Fate, we describe five themes reflecting the formation of a community of HCWs and the social cohesion underlying their efforts to survive hardship. The first three themes characterise the HCW community of fate, including (1) Recognition of extreme work-related danger, (2) physical and figurative closures where HCWs restrict themselves from the outside world, (3) chronic ordeals with overwhelming workload and responsibilities, encompassing recurrent mental health challenges. Against such extreme hardship, cohesive bonding and social resilience are reflected through two additional themes: (4) a mutual sense of moral and professional duty to protect communities, (5) the vertical and horizontal convergence among HCWs across levels and among government departments. We discuss these HCWs’ challenges in relation to systemic vulnerabilities while advocating for increasing investment in public health and collaboration across government sectors to prepare for emergency situations.